STUDIES ON HEPATOPROTECTIVE AND ANTI-INFLAMMATORY ACTIVITY OF COIX LACRYMA–JOBI (LINN) - S, Geetha; Firdous, Jannathul; T, Karpagam; B, Varalakshmi; Priya, Shanmuga; J, Sugunabai; S, Gomathi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: In the present study, evaluation of hepatoprotective activity of Coix lacryma-jobi by CCl4-induced hepatotoxicity test, and evaluation of anti-inflammatory activity of by egg albumin-induced paw edema, and complete Freund’s adjuvant-induced arthritis model were done. Methods: Plant extract was prepared by mixing ethanol with powdered plant seeds and experiment was done as per the procedures of above-mentioned three models. Results: C. lacryma-jobi test extracts out of two doses, 400 mg/kg exhibited a significant reduction in serum cholesterol level as 33 mg/dl when compared to control groups. C. lacryma-jobi seed extract has restored various serological alterations following CCl4-induced hepatotoxicity and was capable of reversing the toxic effects of CCl4 on liver cells. Considerable reduction in the paw volume of exudates observed with C. lacryma-jobi extract, indicating significant anti-inflammatory activity. Conclusion: Therefore, this study shows that C. lacryma-jobs seed extract have anti-inflammatory activity in the models studied.